Effects of nitrogen addition and root fungal inoculation on the seedling growth and rhizosphere soil microbial community of Pinus tabulaeformis - Xu, Lingjie; Niu, Xiaoyun; Li, Xia; Zheng, Yanyan; Feng, Hualei; Fu, Qiang; Zhou, Yong (Frontiers in Microbiology, 2022)
Nitrogen (N) availability is significant in different ecosystems, but the response of forest plant-microbial symbionts to global N deposition remains largely unexplored. In this study, the effects of different N concentration levels on four types of fungi, Suillus granulatus (Sg), Pisolithus tinctorius (Pt), Pleotrichocladium opacum (Po) and Pseudopyrenochaeta sp. (Ps), isolated from the roots of Pinus tabulaeformis were investigated in vitro. Then, the effects of the fungi on the growth performance, nutrient uptake, and rhizosphere soil microbial community structure of P. tabulaeformis under different N addition conditions (0, 40 and 80 kg·hm-2·yr-1) were examined. The biomass and phytohormone contents of the Sg, Pt and Po strains increased with increasing N concentration, while those of the Ps strain first increased and then decreased. All four fungal strains could effectively colonize the plant roots and form a strain-dependent symbiosis with P. tabulaeformis. Although the effects depended on the fungal species, the growth and root development of inoculated seedlings were higher than those of uninoculated seedlings under N deficiency and normal N supply conditions. However, these positive effects disappeared and even became negative under high N supply conditions. The inoculation of the four fungal strains also showed significant positive effects on the shoot and root nutrient contents of P. tabulaeformis. Fungal inoculation significantly increased different microbial groups and the total soil microorganisms but decreased the microbial diversity under N deficiency stress. In summary, exogenous symbiotic fungal inoculations could increase the growth performance of P. tabulaeformis under N deficiency and normal N supply conditions, but the effects were negative under excessive N addition.